Assessment of 11 Exploited Fish and Invertebrate Populations in the Japan Sea Using the CMSY and BSM Methods - Zhang, Shanshan; Wang, Yibang; Wang, Yuanchao; Liang, Cui; Xian, Weiwei (Frontiers in Marine Science, 2020)
The catch-maximum sustainable yield (CMSY) method and a closely-related Bayesian state-space Schaefer surplus production model (BSM) were combined with published catch-per-unit-effort (CPUE) time series or spawning stock biomass (SSB) data to evaluate fisheries reference points for exploited resources of the Japan Sea. Eleven fish and invertebrate stocks were assessed; outcomes obtained through this analysis were the carrying capacity, biomass trajectory, maximum sustainable yield, and related parameters of each stock. Results showed that the stock of Japanese sandfish (Arctoscopus japonicus) was slightly overfished; the stocks of sôhachi (Cleisthenes pinetorum), flathead flounder (Hippoglossoides dubius), bastard halibut (Paralichthys olivaceus) and snow crab (Chionoecetes opilio) were overfished; and the stocks of shotted halibut (Eopsetta grigorjewi), yellow striped flounder (Pseudopleuronectes herzensteini), red seabream (Pagrus major), Alaska pollock (Gadus chalcogrammus) and deep-sea smelt (Glossanodon semifasciatus) were grossly overfished; only Alaskan pink shrimp (Pandalus eous) was in a good condition. These results are consistent with the few previous studies on the status of fish species around Japan, where overfishing is becoming increasingly apparent. These assessments provide a basis for guiding the use of fishery resources in the Japan Sea.